Harnessing Heritage: Educating Communities on the Benefits of Traditional Spices in Bogor Regency - Mareta, Futri Zamnis; Razak, Ismail; Yuaniko, Yuaniko (Santoso Academy Network, 2025)
The use of herbal plants as medicine is one of the efforts to improve public health. The purpose of this community service is to provide counseling on traditional medicinal plants based on local wisdom to the community in Babakanraden Village, Bogor Regency. This counseling is expected to be able to identify the types of medicinal plants, especially those that are widely available in the Babakanraden Village environment. Counseling participants received material exposure through written and picture media about the types of traditional medicinal plants and several traditional medicinal concoctions. Based on the pre-test and post-test scores of the participants, there was a difference in scores of 19%. These results indicate that the participants' knowledge increased after being given counseling. In the future, the people of Babakanraden Village, Bogor Regency, can apply knowledge about traditional medicine, especially that based on local wisdom, as an effort to be independent in preventing disease. The managerial implications of this counseling activity show the importance of the active role of village stakeholders, especially local government officials and public health institutions, in designing and implementing local wisdom-based education programs in a sustainable manner.